(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This study investigated the dangers of erosion to building foundations and human life in Akwa Ibom State, with a focus on identifying effective remedies to mitigate its impacts. It examined how factors such as heavy rainfall, loose soil composition, poor drainage systems, and unplanned human activities have accelerated soil degradation, leading to gully formation, building collapse, and displacement of residents. Expost-Facto design was adopted. The research was carried out in Akwa Ibom State, Nigeria. The targeted population for the study comprised all the environmental scientists in Akwa Ibom State, Nigeria. Stratified sampling technique was used to select 60 Environmental Scientist from each of the senatorial district, this gave a sample size of 180 respondents used to carry out this research. The instrument used for data collection was a structured questionnaire titled “Dangers of Erosion to Building Foundation and Human Life Questionnaire (DEBFHLQ)”. Face and content validation of the instrument was carried out by an expert in test, measurement, and evaluation in order to ensure that the instrument has the accuracy, appropriateness, and completeness for the study under consideration. The reliability coefficient obtained was 0.85, and this was high enough to justify the use of the instrument. Descriptive statistics was used to answer the research question and regression analysis was used to test the hypothesis. The result proved that there is significant effect of erosion on building foundations in Akwa Ibom State. The result also proved that erosion has a significant impact on human life in the State.In conclusion, erosion poses a grave environmental and structural threat to Akwa Ibom State, endangering building foundations and human life through continuous soil degradation, flooding, and gully formation. It was recommended that, government should design and construct efficient and well-connected drainage networks across erosion-prone areas to properly channel storm water and prevent surface runoff from eroding building foundations and surrounding soils.